Jamu as Indonesian Gastronomy: Exploring the Perceptions and Challenges of Generation Z in Gading Serpong - Kezia Elsty; Wiwik Nirmala Sari; Aan Nurhasanah (Universitas Negeri Padang, 2025)
Generation Z (born between 1995 and 2010) holds significant influence over consumption trends, including in the culinary sector. One of Indonesia’s cultural legacies is jamu, a traditional herbal drink known for its health benefits and rich cultural value. However, Generation Z’s interest in jamu, particularly jamu gendong (herbal drinks sold by traditional vendors), tends to be low due to its bitter taste and less appealing appearance. This has led to a decline in jamu consumption among young people. This study aims to explore the perceptions of Generation Z in Gading Serpong towards jamu, as well as the opportunities and challenges related to its preservation. A qualitative descriptive method was employed, utilizing interviews and analytical studies. Informants were selected using purposive sampling, involving 15 university students from various faculties around the Gading Serpong area. Findings indicate that while Generation Z is relatively aware of jamu’s existence, they lack a deeper understanding of its historical and cultural significance. The primary barriers to consumption are its taste and aroma. Nevertheless, jamu still holds potential to be revitalized as part of a modern healthy lifestyle, through